QUALITY OF LIFE OF COVID-19 SURVIVORS IN THE CITY OF BOGOR - Insani, Laras Arsyi; Hidajah, Atik Choirul (The Indonesian Journal of Public Health, 2024)
Introduction: The number of COVID-19 survivors in Bogor City until 2021 is 98.52%. COVID-19 survivors often experience a reduction in quality of life and impacts such as symptoms for a long period of time, fatigue, headaches, shortness of breath, impaired physical function, and others that affect quality of life. Aim: Analyze the quality of life of COVID-19 survivors in Bogor City. Method: A cross-sectional design with a population of all Bogor City residents who have declared cured depending on data from the Bogor City Health Office in 2021 with a sample is the majority of COVID-19 survivors in the Bogor City residents who have been certified cured of COVID-19 as demonstrated by the positive screening findings for COVID-19 and have the inclusion criteria. Age, gender, educational status, marital status, employment status, income, vaccination status, alcohol drinking habit, smoking habit, comorbidity, obesity, COVID-19 symptoms experienced, duration of COVID-19 recovery, and hospitalization were independent variables, and data collection was done with an online questionnaire application within 2 (two) months using the 36-Item Short Form Survey Instrument (SF-36) to measure quality of life. Result: The quality of life of COVID-19 in Bogor City is classified as good. The variables of educational status, income, comorbidities, obesity, COVID-19 symptoms experienced, and duration of COVID-19 recovery show that these variables have a greater risk of experiencing poor quality of life. Conclusion: Educational status, income, comorbidities, obesity, COVID-19 symptoms experienced, and the duration of COVID-19 recovery have a significant relationship with quality of life.